Crete beyond the palaces : proceedings of the Crete 2000 Conference - Day, Leslie Preston; Mook, Margaret S., 1960-; Muhly, James David (Prehistory monographs, 2004)
This volume presents the papers from the conference ""Crete 2000: A Centennial Celebration of American Archaeological Work on Crete (1900-2000), "" held in Athens from July 10-12, 2000. The American School of Classical Studies at Athens and the Institute for Aegean Prehistory (INSTAP) Study Center for East Crete organized the conference. Scholars participating in the American and joint Greek-American excavations on Crete or studying material from these excavations were invited to present papers at the conference. The volume is divided into the following sections: Trade, Society and Religion, Ch